Expression study of stress-related genes in salinity-treated transgenic Arabidopsis harboring soybean Response Regulator 34 - Thai Huyen, Pham Ngoc; Lan Xuan, Hoang Thi; Nguyen Chuong, Nguyen; Phuong Thao, Nguyen (Vietnam Journal of Biotechnology, 2022)
Owing to their sessile nature, plants are easily affected by various extenal factors. Among those, drought and salinity are considered as the most common stresses, which often pose a threat to plant growth and development. Major effects of the drought and salinity are interconnected and drive similar series of molecular changes in plants. These alterations in response to the stress are under the regulation of various signaling pathways, including the engangement of evolutionarily conserved two-component systems (TCSs). Three components with distinct functions can be found in a functional TCS, which are histidine kinases (HKs), histidine-containing phosphotransfer proteins (HPts), and response regulator proteins (RRs). Previous research revealed that the soybean (Glycine max) GmRR34 acts as an important regulatory protein in plants under drought stress conditions. In this project, the investigation on the role of GmRR34 in osmotic stress responses was extended to salinity by examining the expression of a subset of salinity-responsive genes using RT-qPCR method. Our analyses showed that the transgenic Arabidopsis plants ectopically expressing GmRR34 displayed enhanced expression of several important stress-related genes, including Catalase 1 (CAT1), Stromal ascorbate peroxidase 1 (sAPX1), Copper/zinc superoxide dismutase 1 (CSD1), Sodium/hydrogen exchanger 1 (NHX1) and Salt overly sensitive 2 (SOS2). These results indicate that GmRR34-transgenic plants might be more salt-tolerant thanks to stronger activities of antioxidant enzymes and better capacity in maintaining cytosolic ion homeostasis. Therefore, it is highlighted the necessity to perform further studies to fully characterize the GmRR34 biological functions as well as explore its application potential in enhancing the salt tolerance of crop plants.